APLIKASI MEDIA GAMBAR BERSERI PADA PEMBELAJARAN TEMATIK TERPADU KELAS IV SEMESTER II TEMA PAHLAWANKU SD NEGERI BOLO DEMAK - Nurul Ariyanti, Kiswoyo (MALIH PEDDAS, 2015)
This research is motivated by the lack of media use are causing varying levels of students understanding of the material becomes less , and students feel tired and less interested in learning a given. The problem in this study is How the media application on the radiant image of integrated thematic teaching fourth grade second semester Elementary School Heroes theme Bolo Demak in the Academic Year 2013/2014? The purpose of this study was to describe the radiant image media applications on integrated thematic learning fourth grade second semester Elementary School Heroes theme Bolo Demak in the Academic Year 2013/2014. This research uses descriptive qualitative research approach. Location of the study in Demak Bolo Elementary School fourth grade second semester. Data sourced words research results. The results showed no improvement in student evaluation of learning outcomes 4, 5, and 6 using media images beamed on learning Heroes theme. The average value of classical ie increased 85,7 % which exceeds the results of complete classical limit above 75% of all students. Observations of teachers learning to use the media images have an average radiant with the criteria of